2016
DOI: 10.2174/1874155x01610010183
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Mechanical Properties of Tires for Wheelchair Simulation

Abstract: The development of high performance wheelchairs and wheelchair simulators requires dynamic models taking into account the properties of tires. In this paper the properties of two wheelchair tires are measured by means of a rotating disc testing machine and are compared with the properties of bicycle tires, which have similar dimensions and structure. Tests are carried out considering variations in speed, inflation pressure and load. The possibility of fitting experimental results with the Magic Formula, the Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The four qualitative statements cohere with both the following dynamical analysis and recent wheelchair tyre property investigations [8], [9], [10]. A preliminary observation for assisted wheelchairs is that all dynamic actions are handle forces.…”
Section: Coherent View Of Lateral Driftsupporting
confidence: 78%
See 4 more Smart Citations
“…The four qualitative statements cohere with both the following dynamical analysis and recent wheelchair tyre property investigations [8], [9], [10]. A preliminary observation for assisted wheelchairs is that all dynamic actions are handle forces.…”
Section: Coherent View Of Lateral Driftsupporting
confidence: 78%
“…It is therefore concluded that during push turns, lateral handle force and caster wheel motion resistance contributed to the resulting lateral drift away from curvature centre. Nevertheless, it is also reasonably concluded that the tyre property effects [8], [9] and [10] present for pull turns, were present for push turns. Push and pull turn lateral drift magnitudes therefore differed.…”
Section: Coherent View Of Lateral Driftmentioning
confidence: 82%
See 3 more Smart Citations